EXAMINING THE REGULATIONS GOVERNING OFFSHORE DECOMMISSIONING IN FIVE COUNTRIES ADVANTAGES AND DISADVANTAGES - Saputra, Eno; Anggara, Ari; Husaini, Husaini; Salasa, Ricco; Haryadi, Donni; Rafik, M.; Fikri, KMS Novyar Satriawan (Yayasan Education and Social Center, 2025)
In the decades ahead, the decommissioning of offshore structures worldwide will remain a persistent issue, as numerous structures will surpass their expiration or become unproductive when reservoirs are no longer utilized. This article analyzes the global offshore decommissioning legal framework and summarizes the rules in countries recognized for their expertise in decommissioning, specifically the UK, Norway, and the USA. The oil-producing nations of Malaysia and Thailand in Southeast Asia are examined to uncover potential deficiencies in decommissioning legislation for countries at the nascent decommissioning stage. The distinctions were recognized regarding decommissioning preparation, technical execution of decommissioning, supplementary environmental standards, and the financial security framework. In conclusion, most legislation about the technical sector is analogous throughout all examined countries. Significant distinctions exist between two primary philosophies of the framework: a prescriptive regime and a goal-setting regime. Other decommissioning facets garner heightened scrutiny, including the elucidation of in situ decommissioning, residual liabilities, the optimization of financial considerations associated with decommissioning, and the transfer of waste from offshore to onshore. The deficiencies in the current framework can be addressed by adopting an evidence-based approach in its development